Participación política de la mujer colombiana, y el compromiso de las Escuelas de Administración - Aura Janeth Uribe Aréval; Julio Alberto Perea Sandoval (Mundo Fesc)
This research seeks to understand the political participation of women and how they have been linked to the country's political scene. In parallel, this study aims to reflect on the role that Business Administration programs should assume in raising awareness among their students towards political participation, acquiring a critical vision of the country's reality and recognizing the importance they assume in political participation in their regions of origin and as future leaders of the organizations in which they will practice their profession. The methodological approach is marked by a descriptive documentary route through the analysis of documentary sources. This research has allowed us to envision the need for greater involvement in political and sustainability training among university students, particularly by highlighting the role of women in their communities and regions as agents of change. The results showed that women have been rendered invisible, and because they are stereotyped as fragile and dependent, their chances of participating in political life are diminished, or they are simply not considered for these types of positions. Additionally, in the last and present centuries, the OSDs, in their need for equality and equity, have given them tools to fight for the recognition of their rights. University business schools are a place where they can prepare and acquire skills that enhance their capacity for struggle, responsibility, and commitment to society. In conclusion, women throughout history have been able to demonstrate through achievements their capabilities in participating in the country's political life. Women have known how to empower themselves, lead, contribute ideas, and make decisions, which has led them to become increasingly visible.